Therapy of the Epic Trauma Through Narrative - Harmanci, Meric; Arican, Sumeyya (GELENEKSEL YAYINCILIK LTD STL, 2024)
The world consists of societies that tell of the pain, floods, disasters, and traumas they have experienced throughout history. The individual or organization experiences disaster; he feels the pain, registers it in his memory, and takes action to repair the spiritual destruction. One of the tools of this repair phase is narratives. There is a close relationship between human mental health and the act of telling. This verbal plane contains the answer to the question, why does a person tell. The word has a talismanic and healing property. Narration; should be understood as an expression technique and a method of spiritual therapy, regardless of the medium, such as words, writing, painting, or dance. The act of telling is an indispensable element of healing, although it is one of the therapy methods. A human who does not tell their troubles will not find a cure; sequence that can follow humans from ancestor aphorisms such as love makes one cry, concerns relate, psychologist-client interview techniques and therapy methods; narration, narratives, writings, words, emphasizes the importance of many transmission pathways. When the sequential triangle of trauma therapy in epics, one of the ancient forms of narration, is considered a structural plane, it should mention functionality of literary trauma theory. Epic texts, which focus on a social function, also serve the purpose spiritual healing and recovery from trauma in all circumstances. The epic embodies black and white, like dichotomy of the universe and human beings. If there is a person, there is also pain; naturally, in this case, can also reveal trauma. When we think of trauma as a state of lockdown, we can see epic as a state of dissolution. In this article, the therapeutic function of the epic, which is one of the narrative genres, will be discussed. Social turning points intertwine with the epic; this intersection arises from the need to tell and offers various forms of healing. As all painful events such as earthquakes, droughts, migration, war, loss of a loved one society, and sudden deaths narrate, it becomes a permanent cultural heritage and offers therapy opportunities. It is also possible to talk about the long-term transformation of the therapy realized through the epic narrative into a social design. Through these narratives, societies not only remove the traces of the pain they learned and experienced while passing through traumas but also inform future generations of the traumatic intersections that may come their way. The experience of these traumas lay behind the implicit suggestion warning that was abstracted by the narrative and turned into an ideal. It is a desire to prepare society for traumas by advancing on the path of this constantly repeated ancient transference. The community in process of formation and spread of the epic and the ancestral lineage of the epic also recover through the and by following the signs sent years ago, they get the opportunity to protect themselves. This environment trust realizes with the epic narrative born in an insecure environment. Just as every destruction marks a beginning, epics born after an uncertain environment become a means of healing for various people societies. This study reveals the traumas that turned into an epic text hidden behind the narrative today and function in the context of community therapy, and its transformation into a vision project. The epic, born nourished by chaos, reveals the pain of experiencing trauma while mediating the treatment of generations the healing of societies with its permanence.
Keywords: Key Trauma; social trauma; memory; epic; therapy; Arts & Humanities - Other Topics